2020
DOI: 10.21037/apm-19-479
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical effects and safety between the distal radial artery and the classic radial artery approaches in percutaneous coronary intervention

Abstract: Background: Compared with a classic wrist puncture for radial artery catheterization, a distal radial artery puncture has the advantage of reducing the incidence of radial artery occlusion in anatomic and physiological procedures. This study aimed to explore the difference in clinical effects between the distal radial artery and classic radial artery approaches in percutaneous coronary intervention.Methods: A total of 620 patients who underwent coronary angiography and/or percutaneous coronary intervention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 10 publications
3
29
1
Order By: Relevance
“…According to our findings, Wang et al [ 21 ], the mean puncture time for d-TRA was 5.4 ± 1.6 min and 5.6 ± 1.4 min for TRA, and the mean operational time for d-TRA and TRA was 50.0 ± 8.3 min and 51.0 ± 7.9 min, respectively. They also discovered that there were no significant differences in puncture success rate, puncture time, or operation duration between the two groups ( P > 0.05).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…According to our findings, Wang et al [ 21 ], the mean puncture time for d-TRA was 5.4 ± 1.6 min and 5.6 ± 1.4 min for TRA, and the mean operational time for d-TRA and TRA was 50.0 ± 8.3 min and 51.0 ± 7.9 min, respectively. They also discovered that there were no significant differences in puncture success rate, puncture time, or operation duration between the two groups ( P > 0.05).…”
Section: Discussionsupporting
confidence: 78%
“…Wang et al [ 21 ] also found that among the 160 males and 152 females in the distal radial artery puncture group, the average age was 50.17.2 years. There were 157 males and 151 females in the radial artery puncture group, with an average age of 51.27.3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Wang et al of 620 patients who underwent PCI with either conventional TRA or dRA approach, there was no significant difference in puncture time, puncture success rate, procedure time, puncture site hemorrhage, hematoma and aneurysm but RAO was significantly lower in dRA access (p < 0.05). 16 Similar findings were observed in a metanalysis of five studies (four observational and one randomized trial), with a total of 4676 patients. 17 The rate of RAO was lower with dRA approach (2.30 versus 4.86%, RR = 0.51; 95%CI 0.32–0.81; p = 0.004) as compared to conventional TRA.…”
Section: Clinical Considerationssupporting
confidence: 75%
“…The meta-analysis showed compared with cTRA, the access time was longer in dTRA, with the statistical difference between studies (SMD = 0.32, 95CI [0.08, 0.56], P =0.008; I 2 = 86.7%, P < 0.001) (see Figure 6 ). We conducted a sensitivity analysis by removing the outlier study, heterogeneity was significantly reduced after excluding the study by Wang [ 22 ], and there was still a statistical difference (SMD = 0.41, 95CI [0.29, 0.54], P < 0.001; I 2 = 32.5%, P =0.205). The Egger test showed no publication bias among the studies ( P =0.463).…”
Section: Resultsmentioning
confidence: 99%